2007
DOI: 10.1542/peds.2006-2819
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Functioning and Coping Among Mothers of Children With Autism: A Population-Based Study

Abstract: Mothers of children with autism showed remarkable strengths in the parent-child relationship, social support, and stability of the household in the context of high stress and poorer mental health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
191
3
15

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 294 publications
(216 citation statements)
references
References 15 publications
7
191
3
15
Order By: Relevance
“…Similar to the extant literature (Gray, 1994(Gray, , 1997Hutton & Caron, 2005, Montes & Halterman, 2007Phelps, et al, 2009), the parents of young children with ASD in our study reported impaired family functioning in several ways. For example, mothers spoke of how difficult it is to do normal or spontaneous family activities, because family life with a child with ASD has to be very structured and planned.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Similar to the extant literature (Gray, 1994(Gray, , 1997Hutton & Caron, 2005, Montes & Halterman, 2007Phelps, et al, 2009), the parents of young children with ASD in our study reported impaired family functioning in several ways. For example, mothers spoke of how difficult it is to do normal or spontaneous family activities, because family life with a child with ASD has to be very structured and planned.…”
Section: Discussionsupporting
confidence: 88%
“…The children's restricted social, communicative and emotional competencies, their uneven cognitive development, and their maladaptive behaviour place tremendous stress on parents of children with ASD (Davis & Carter, 2008;Hastings & Johnson, 2001). In comparison to mothers of typically developing (TD) children and mothers of children with other disabilities, mothers of children with ASD report elevated stress levels (Eisenhower, Baker, & Blacher, 2005;Estes, et al, 2009;Montes & Halterman, 2007;Rao & Beidel, 2009) and they are at an increased risk for depression (Olsson & Hwang, 2001). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings indicated that autistic group gained higher scores on the Alexithymia questionnaire (Szatmari, 2008). In contrast, some studies do not support the impact of having autistic children in parents' adaptation (Montes & Halterman, 2007). Despite the widespread interest in studying the autism phenotype, there is now no consensus on its definition (Scheeren & Stauder, 2008).…”
Section: Literature Reviewmentioning
confidence: 95%
“…Research has shown that the severe and pervasive impairments in communication and social interaction and the maladjusted behaviour in children with autism spectrum disorder (ASD) are a significant source of stress and depressive symptoms for parents of a child with ASD (Eisenhower et al, 2005;Estes et al, 2009;Montes & Halterman, 2007;Olsson & Hwang, 2001;Rao & Beidel, 2009). These impairments and the stress involved also have a considerable impact on parent's interactive behaviour (Hoppes & Harris, 1990;Kasari & Sigman, 1997).…”
Section: Introductionmentioning
confidence: 99%